Contemporary sites of contemplation: contemplative nature of the aesthetic experience of natural and transformed landscape in Roden Crater by James Turrell and Lucid Stead by Philip K. Smith - Issa, Nadia (Polskie Studia Krajobrazowe, 2019)
The aim of this paper is to offer an interpretation of two contemporary art works: James Turrell’s Roden Crater and Philip K. Smith’s Lucid Stead. They are seen as projects that may be qualified as examples of art based on the artists’ playing with light. The claim being that one of the factors that engenders a contemplative attitude on behalf of the beholder is the presence of light in relation to the artwork’s structure.